PERBEDAAN PERILAKU SEKS BEBAS REMAJA DITINJAU DARI TIPE POLA ASUH ORANG TUA DI SMK BATIK 1 SURAKARTA - Meylsa Rima Kamilda (Universitas Muhammadiyah Tangerang, 2018)
ABSTRACTBackground: Adolescents experience physical changes which encourage sexual drive due to reproductive organ maturity. Uncontrollable sexual drive can lead to free sex. The free sex behaviors of the adolescents can be controlled by many ways, and one of which is the appropriate parenting pattern implementation. The objective of this research is to investigate the free sex behaviors of the adolescents viewed from the parenting pattern types.Method: This research used the observational analytical research method with the cross sectional approach. It was conducted at Vocational High School Batik 1 of Surakarta. The samples of research consisted of 97 respondents who fulfilled the inclusion and exclusion criteria and were determined through the cluster random sampling technique. The independent and dependent variables of the research were parenting pattern respectively and free sex. The data of research were analyzed by using the Kruskal Walls’s test aided with the computer program of SPSS 22.0.Result: 9 respondents out of 16 cared with the authoritarian parenting pattern had the free sex behaviors, 23 out of 73 respondents cared with the authoritative parenting pattern had the free sex behaviors, and 4 out of 8 respondents cared with the permissive parenting pattern had the free sex behaviors. The result of the statistical analysis with the Kruskal Wallis’s test shows that p-value was 0.349, and the p-value was less than 0.05.Conclusion: There was not a difference of free sex behaviors of the adolescents viewed from the parenting pattern types at Vocational High School Batik 1 of Surakarta (p= 0. 349>0.05). Keywords: Free sex behaviors, parenting pattern, adolescents